BOMB PENETRATION TESTS, FORT CHURCHILL, CANADA. - Livingston,Clifton W. (1960)
Inert mortar shells and inert general-purpose, semi-armor-piercing, and armor-piercing bombs were dropped on frozen ground (glacial till) near Fort Churchill, Manitoba. Canada during the winter 1956-57 to observe projectile penetration and determine the feasibility of forming trenches and foxholes in frozen ground by means of bombs released from aircraft. Projectiles ranging from 81-mm mortar shells to 1600 AP bombs were released from altitudes of 2000 to 24,500 ft. Analysis of the test data was directed towards determining fundamentals of penetration of projectiles into materials of the earth's crust. (Author)